Interactions Between Figs and Gall-Inducing Fig Wasps: Adaptations, Constraints, and Unanswered Questions - Borges, Renee M. (Frontiers in Ecology and Evolution, 2021)
The ancient interaction between figs (Ficus, Moraceae) and their pollinating fig wasps is an unusual example of a mutualism between plants and gall-inducing insects. This review intends to offer fresh perspectives into the relationship between figs and the diversity of gall-inducing sycophiles which inhabit their enclosed globular inflorescences that function as microcosms. Besides gall-inducing pollinators, fig inflorescences are also inhabited by other gall-inducing wasps. This review evaluates the state of current knowledge on gall-induction by fig wasps and exposes the many lacunae in this area. This review makes connections between fig and gall-inducing wasp traits, and suggests relatively unexplored research avenues. This manuscript calls for an integrated approach that incorporates such diverse fields as life-history theory, plant mate choice, wasp sexual selection and local mate competition, plant embryology as well as seed and fruit dispersal. It calls for collaboration between researchers such as plant developmental biologists, insect physiologists, chemical ecologists and sensory biologists to jointly solve the many valuable questions that can be addressed in community ecology, co-evolution and species interaction biology using the fig inflorescence microcosm, that is inhabited by gall-inducing mutualistic and parasitic wasps, as a model system.